2000
DOI: 10.1074/jbc.m004160200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Human Acetyl-CoA Synthetase, an Enzyme Regulated by Sterol Regulatory Element-binding Proteins

Abstract: Through suppressive subtractive hybridization, we identified a new gene whose transcription is induced by sterol regulatory element-binding proteins (SREBPs). The gene encodes acetyl-CoA synthetase (ACS), the cytosolic enzyme that activates acetate so that it can be used for lipid synthesis or for energy generation. ACS genes were isolated previously from yeast, but not from animal cells. Recombinant human ACS was produced by expressing the cloned cDNA transiently in human cells. After purification by nickel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
204
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(219 citation statements)
references
References 42 publications
10
204
0
1
Order By: Relevance
“…The signal decay of precursor and metabolites results from a combination of the effects of longitudinal relaxation (characterized by the time constant T 1 ), RF excitation, and biochemical conversion and all time courses were corrected for the effect of repeated RF excitations. The T 1 of [1-13 C]acetylcarnitine was set to 14.9 s, as previously determined in vivo [35], and that of [5][6][7][8][9][10][11][12][13] C]citrate to 20 s [46]. The acetate signal decay was treated as free parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal decay of precursor and metabolites results from a combination of the effects of longitudinal relaxation (characterized by the time constant T 1 ), RF excitation, and biochemical conversion and all time courses were corrected for the effect of repeated RF excitations. The T 1 of [1-13 C]acetylcarnitine was set to 14.9 s, as previously determined in vivo [35], and that of [5][6][7][8][9][10][11][12][13] C]citrate to 20 s [46]. The acetate signal decay was treated as free parameter.…”
Section: Discussionmentioning
confidence: 99%
“…It is the shortest fatty acid and its uptake into the heart occurs through simple diffusion, its exchange between plasma and tissue only depending on the concentration gradient [5]. It is an effective oxidizable substrate formed endogenously that can be activated to acetylCoA via cytosolic or mitochondrial acetylCoA synthetase [6,7]. The cytosolic variant of acetylCoA synthetase is mainly present in the liver, while the mitochondrial variant is abundant in the heart and muscle and provides acetylCoA that is utilized mainly for oxidation under ketogenic conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…One of these acetyl kinases is a cytosolic acetyl-CoA synthetase 1 (AceCS1). It produces acetyl-CoA, which is active only in fatty acid synthesis, is highly expressed in the liver and is regulated by the same factors and patterns as FAS [14]. The other (AceCS2) is an enzyme bound to the mitochondrial matrix, found abundantly in hearts and kidneys, and synthesising acetyl-CoA active in the TCA cycle and producing [ 14 C]CO 2 from [ 14 C]acetate [15].…”
Section: Acetate Metabolic Routsmentioning
confidence: 99%
“…It is interesting to note that the authors who discovered human AceCS have found that from the screened 95 different cell lines AceCS1 was most abundant in human adenocarcinoma of the colon [14].…”
Section: Acetate Metabolic Routsmentioning
confidence: 99%
See 1 more Smart Citation